Implementation of Point-of-Care Testing in an Ambulatory Practice of an Academic Medical Center. Issue 5 (August 2015) - Crocker, J. Benjamin; Lee-Lewandrowski, Elizabeth; Lewandrowski, Nicole; Baron, Jason; Gregory, Kimberly; Lewandrowski, Kent
Abstract : Objectives: Point-of-care laboratory testing (POCT) offers reduced turnaround time and may promote improved operational efficiency. Few studies have been reported that document improvements from implementing POCT in primary care. Methods: We measured metrics of practice efficiency in a primary care practice before and after implementation of POCT, including the total number of tests ordered, letters and phone calls to patients, and revisits due to abnormal test results. We performed a cost and revenue analysis. Results: Following implementation of POCT, there was a 21% decrease in tests ordered per patient ( P < .0001); a decrease in follow-up phone calls and letters by 89% and 85%, respectively ( P < .0001 and P < .0001); and a 61% decrease in patient revisits ( P = .0002). Estimated testing revenues exceeded expenses by $6.62 per patient, and potential cost savings from improved efficiency were $24.64 per patient. Conclusions: POCT can significantly improve clinical operations with cost reductions through improved practice efficiency.